Good survival of broadleaf tree species in a four-year-old plantation in the Slovenian Karst - Škrk, Nina (Acta silvae et ligni, 2022)
Six broadleaf tree species (Celtis australis L. – Mediterranean hackberry, Quercus petraea (Matt.) Liebl. – sessile oak, Fagus sylvatica L. – European beech, Prunus avium L. – wild cherry, Juglans regia L. – Persian walnut and Acer pseudoplatanus L. – sycamore maple) were planted in 2012 in a trial in the Slovenian Karst on two sites differing in productivity to test their suitability for use in the conversion of old pine stands into ecologically more stable broadleaf forests and to investigate their possible response to the harsher growth conditions predicted in the future. The selected economically interesting tree species have higher timber quality than broadleaves which regenerate naturally (e.g., Ostrya carpinifolia, Fraxinus ornus, Quercus cerris). Measurements were taken in 2017, after four growth seasons. All planted species except Fagus sylvatica had a high survival rate. In total, 70% of all seedlings survived, which shows promising potential. The survival rate was higher at the site on flat terrain than at the site on a slope. Prunus avium was the most successful of all planted species in terms of survival rate, at 83%, and other measured parameters (height, height increment, stem diameter, vitality and quality), and Fagus sylvatica was the least successful, with a survival rate of only 20%. Celtis australis had the highest survival rate, at 87%. Acer pseudoplatanus had the largest differences in measured parameters between the more and less productive sites among all planted species. Quercus petraea showed high resistance to xeric conditions and is expected to be the most successful in conversions. All planted species except Fagus sylvatica show favourable initial potential for the future conversion of Karst pine forests.
Keywords: broadleaves; climate change; delež preživetja; forest conversion; kakovost sadik; listavci; podnebne spremembe; premena gozda; seedlings quality; survival rate